Exploring the factors that contribute towards better student-mentor relationship in work-based learning (WBL) practice - Mohabuth, Abdool Qaiyum (Journal of Education and Vocational Research, 2015)
Mentors are called upon to counsel, guide, coach and advise mentees. Mentoring creates a relationship with the purpose of facilitating learners to achieve their learning goals. It allows individuals to look objectively at their performance and future development. Mentoring takes a formal setting in WBL practice which involves an experience for learning and a change in which mentor and mentee utilize a range of core components including honesty, trust and respectful listening to transfer knowledge and skills. Students on WBL practice view mentors as the right professionals with advanced work experience and knowledge from whom they may seek assistance for their professional and personal development. While many students undertaking WBL practice have experienced positive mentoring, there are some that complain about the lack of attention and care provided by their mentors. Most studies investigated the antecedents, outcomes, and benefits of programs with little attention given to identifying and illustrating what is required to ensure the quality of the mentoring process and the effectiveness of the mentoring relationship. This study sought to identify the factors that contribute towards positive mentoring for enhancing the student-mentor relationship. A survey questionnaire was designed for exploring the factors that lead to positive mentoring in WBL practice. The questionnaire was administered to students of the University of Mauritius who undertook WBL practice at the respective placement settings. Mentors providing the necessary coaching at these practice settings were also requested to complete a questionnaire. The findings reveal a list of the main factors which can lead to successful mentoring and enhance the student-mentor relationship. The element of ‘trust’ was found to be the most influential factor in the relationship, followed by ‘empathy’ and ‘openness’. These factors are seen to enhance interactive capability of mentees which contribute much towards improved acquisition of knowledge and skills in the practice.